Assessment of derived emission limits for radioactive effluents resulted from the decommissioning activities of the VVR-S nuclear research reactor - Tuca, C.; Stochioiu, A.; Sahagia, M.; Gurau, D.; Dragusin, M. (Journal of environmental radioactivity, 2015)
This paper presents complex studies on establishment of derived emission limits for potential radionuclides emitted as gaseous and liquid effluents, during the decommissioning activities (2nd and 3rd phases) of a nuclear research reactor, cooled and moderated with distilled water, type VVR-S, owned by the IFIN-HH. In the present paper there are described: the analysis methods and equipment used, the methodologies for calculating doses and the Derived Emission Limits (DEL), the experimentally measured activities of the representative radionuclides found in gaseous and liquid effluents resulted from decommissioning activities, as well as the effective derived limits of liquid and gaseous effluents, applying the calculation methodologies, specific to critical categories of exposed subjects. A constraint effective dose limit for a person from the critical group of 50 μSv/year was considered in calculations. From the comparison of the two series of values, measured released activities and DELs, there has been concluded that for the gaseous effluents they comply with the DELs, while in the case of liquid effluents they are higher and consequently they must be treated as liquid radioactive wastes. •The DELs for gaseous and liquid effluents in decommissioning were studied.•The impact on the environment and critical group was assessed.•Gamma-ray spectrometry was used to determine the radionuclide composition.•Based on the dosimetry models, the values of conservative DELs were calculated.•The DELs are compliant for gases, not for liquids; require the treatment as rad-waste.